2017
DOI: 10.3390/en10122164
|View full text |Cite
|
Sign up to set email alerts
|

Flow Adjustment Inside and Around Large Finite-Size Wind Farms

Abstract: Abstract:In this study, large-eddy simulations are performed to investigate the flow inside and around large finite-size wind farms in conventionally-neutral atmospheric boundary layers. Special emphasis is placed on characterizing the different farm-induced flow regions, including the induction, entrance and development, fully-developed, exit and farm wake regions. The wind farms extend 20 km in the streamwise direction and comprise 36 wind turbine rows arranged in aligned and staggered configurations. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
117
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(167 citation statements)
references
References 60 publications
19
117
4
Order By: Relevance
“…The hub-to-hub distances in the wind tunnel were generally tight compared to modern wind farms (2.66 D laterally and 4 D streamwise, with D = rotor diameters), and there is also risk that the wind tunnel walls could influence the observed blockage. That said, large-eddy simulation results from two recent studies, [13,14], both showed significant wind speed decreases upstream of infinitely wide, full-scale wind farms. Allaerts [13] attributed the upstream flow decelerations to adverse pressure gradients induced by gravity waves.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The hub-to-hub distances in the wind tunnel were generally tight compared to modern wind farms (2.66 D laterally and 4 D streamwise, with D = rotor diameters), and there is also risk that the wind tunnel walls could influence the observed blockage. That said, large-eddy simulation results from two recent studies, [13,14], both showed significant wind speed decreases upstream of infinitely wide, full-scale wind farms. Allaerts [13] attributed the upstream flow decelerations to adverse pressure gradients induced by gravity waves.…”
Section: Introductionmentioning
confidence: 97%
“…Allaerts [13] attributed the upstream flow decelerations to adverse pressure gradients induced by gravity waves. Wu [14] also attributed upstream deficits to gravity waves, but also to cumulative turbine induction, with the balance between the two influences strongly dependent on atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the staggered layout was found to produce the highest power output, showing good agreement with wind tunnel experiments of aligned and staggered wind farms [13-15]. Stevens et al [16] investigated the effect of changing the alignment angle with the wind direction of originally streamwise oriented turbine columns.It was found that an alignment angle smaller than fully staggered can result in an overall higher power output, indicating that a staggered layout is not necessarily the most optimal.While the layout clearly influences the power of the first few rows of the farm, LES results [16][17][18] and wind tunnel measurements [14,15] show that after approximately ten rows, the average row-power becomes independent of row number, thus indicating the approach of a fully-developed regime.…”
mentioning
confidence: 99%
“…While the layout clearly influences the power of the first few rows of the farm, LES results [16][17][18] and wind tunnel measurements [14,15] show that after approximately ten rows, the average row-power becomes independent of row number, thus indicating the approach of a fully-developed regime.…”
mentioning
confidence: 99%
“…The theory presented above is based on the assumption that the flow over the turbine array is in a fully developed state, i.e., the same local flow pattern around each turbine is repeated over the entire farm (except for the farm edge region). In reality, however, the flow over the array may not be fully developed and the flow pattern around each turbine may vary over the entire farm, depending on, for example, the atmospheric stability conditions (Wu and Porté-Agel, 2017). This assumption may also be violated simply due to an irregular turbine arrangement, variation of turbine operating conditions and/or inhomogeneity of the natural atmospheric flow over the farm area.…”
Section: Horizontal Variations Across the Farmmentioning
confidence: 99%